Correction of recurrent dislocation of the mandible in elderly patients by the Dautrey procedure - H. Kobayashi,* T. Yamazaki, H. Okudera, (Blackwell Synergy, 2000)
Dislocation of the temporomandibular joint (TMJ) is caused by displacement of the condyle in front of the articular eminence. Patients sometimes cannot replace it themselves and often require reduction under general anaesthesia.